2017
DOI: 10.1049/el.2017.0950
|View full text |Cite
|
Sign up to set email alerts
|

Predicted and measured temperature compensated surface acoustic wave devices for high‐temperature applications

Abstract: Industrial monitoring and process control, power plants, aerospace industry, military equipment manufacturing, oil and gas industries are examples of businesses in need for high-temperature and harshenvironment electronic components and systems. In particular, resonators and filters that operate beyond the 125°C military range upper limit, normally dictated by silicon-based semiconductor devices, are required in applications which demand frequency control, clocking and sensors. In this Letter, temperature comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Another important factor in determining the viability of materials for computing is their thermal stability. Semiconductor-based electronic devices used in industrial, commercial, and military applications commonly require operability up to 125 °C. , Thus, to assess the feasibility of using SiNSs in computing applications, we sought to characterize the thermal stability and optical properties of the SiNSs after exposing them to a range of elevated temperatures.…”
mentioning
confidence: 99%
“…Another important factor in determining the viability of materials for computing is their thermal stability. Semiconductor-based electronic devices used in industrial, commercial, and military applications commonly require operability up to 125 °C. , Thus, to assess the feasibility of using SiNSs in computing applications, we sought to characterize the thermal stability and optical properties of the SiNSs after exposing them to a range of elevated temperatures.…”
mentioning
confidence: 99%
“…[16,23,24] To meet the requirements for commercial level memory devices, the PVA films should be stable in the temperature range of −45 to +85 °C (general use) as well as −55 to +125 °C (aerospace and military applications). [25][26][27][28][29][30] However, it has been reported that the transistor devices with the PVA films as a memory layer were unable to keep memory performances owing to poor hysteresis characteristics upon exposure to high temperature conditions because the PVA chain alignment was significantly deformed by thermal relaxation at temperatures higher than the glass transition temperature of PVA (T g = 85 °C). [31][32][33][34] In order to overcome this problem, cytochrome c (cyt c) has been introduced to anchor the PVA chains, which led to the improved thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature can vary from À20 C to 85 C in typical electronic devices and sometimes within a much larger range, like in military applications. 1,2 The typical temperature range for piezoelectric actuators in fuel injection systems, for example, is from À55 C to 150 C. 3 Such temperature variations can significantly change the electromechanical behavior of ferroelectric materials through variations in both the intrinsic and extrinsic contributions. The characterization of ferroelectrics under temperature is, therefore, a key point for the design of engineered devices that use ferroelectrics.…”
Section: Introductionmentioning
confidence: 99%